Kinerja manajerial: Peranan strategic management accounting dan pengaruh intelektual capital terhadap kinerja keuangan - Lestari, Fitri; De Han, Nikita Yasmin; Kurnianingsih, Heny Triastuti (Proceeding of National Conference on Accounting & Finance, 2024)
This research aims to review the role of management accounting strategies and the impact of intelektual capital strategies on financial performance results. The data we currently use is still the result of research from 23 accounting journals that the author has read. In order to produce more accurate data, we will add reviews of previous accounting journals. The results of this research indicate that strategic management accounting that uses intelektual capital has important implications for financial performance in both goods and services companies.